(untitled) (The Journal of Psychology and Sociology, 2017)
Portrait of a modern information society forms such as the deconstruction trend, globalization, mass character, contamination of power and knowledge, anesthetization and virtualization. In the era of Internet gadgets discourse through the high-tech revolution has spawned a new digital technology and designed another politics, economy, culture and sociality. The other – digital (electronic) economy means by digital telecommunications. Electronic economy is different from the real economy by the existence in cyberspace and dependence on telecommunication networks and computer equipment. The main advantages of the e-economy – is the highest growth rate and the speed of information dissemination within the e-economy. The main advantages of e-economy- are high growth rates and speed of information dissemination within the e-economy. In Kazakhstan, in May 2016, were completed the development of the state program «Digital Kazakhstan-2020», which shall operate on the basis of public-private partnerships. The program «Digital Kazakhstan-2020» includes 2 stages: 1. Preparation of the foundation (2016-2019) and 2. Start the project by industry (2020-2025). In Korea, in 1994 the Government established the Policy Committee of the Korean Information Infrastructure (KII) and 3 of the master plans on the development of the information society: 1. Development of Information (1996-1998.) ; 2. Cyber-21 Korea (1999-2002.) ; 3. E-Korea 2006 tasks (2002) : Digital education can be presented in different ways: in terms of new economic education; education in a digital world in general; education on successful countries; learning from their mistakes, too; education sector as a sector of the digital economy. Key words: digital age, cyberspace, digital economy and education